IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI DI DESA POLEWALI KECAMATAN BAMBALAMOTU KABUPATEN MAMUJU UTARA - Syamsuddin, Syamsuddin (Katalogis, 2016)
The National Program Independent Community Empowerment is one of the government policies in alleviating poverty and providing works by involving communities in all stages of the development, from planning, actualization, monitoring to evaluation. Through the participatory development, the community critical awareness and self-reliance, particulary the poor communities, can be increased so that they will not merely become the objective of development programs but also as the subjects in combating poverty efforts at the same time. This research describes the implementation of the National Program Independent Community Empowerment, the result shows that the implementation of the National Program of Rural Community Empowerment in Polewali Village can be categorized good in general despite some of its weaknesses. The interpretation of the implementation of the National Program Independent Community Empowerment in Polewali Village is still not well understood both by the activities manager in village level and the villagers themselves. The aplication of the National Program Independent Community Empowerment in Polewali Village has been able to carried out , although there are still some obstacles faced.